Our racist heart?: an exploration of unconscious prejudice in everyday life - Beattie, Geoffrey (Routledge, 2013)
Introduction : approaches and avoidances -- A room steeped in the past -- Early lessons in prejudice : spoken and unspoken -- Who needs a Negro? -- The nature of prejudice -- The times they are a changin' (or not, as the case may be) -- The inner conflict -- How much of our attitude is unconscious? -- Measuring the conscious -- A new way into our unconscious attitude -- By-passing the conscious mind -- A new test of implicit ethnic bias -- New data on possible implicit ethnic bias -- Am i racist? -- Why aren't we saving the planet? : another example of unconscious bias in action -- How ethnicity and implicit attitudes may affect shortlisting for university posts -- So what can we do about all this?